Developing Green Marketing Strategies: A Comprehensive Analysis of Consumer Behaviour and Business Practices - Mansour, Ahmad; Al-Ahmed, Hind; Deek, Anan; Alshaketheep, Khaled; Al-Ma’aitah, Mohammad; Asfour, Bara; Alshurideh, Muhammad (International Review of Management and Marketing, 2024)
The purpose of this research is to examine the relationship between green marketing communication techniques, consumer behaviour patterns, and business organisations’ practices by employing both qualitative and quantitative methodologies. A hypothesized quantitative survey with 500 consumers and a qualitative case study of leading organisations to assess modern tendencies and approaches were carried out. The quantitative analysis shows that 70% of the consumers take environmental concern while purchasing products, but only 45% are ready to pay the premium price for green products. Moreover, there is a low level of confidence in green claims where only 30% of the consumers are confident that firms have sincere intentions about the statements they make. An analysis of Nike, Starbucks, and Toyota, Apple, and Microsoft organizations shows that they incorporate different strategies in supply chain management, carbon footprint, corporations’ responsibility, and customer relations. Some of these firms focus on the promotion of the company’s transparency, product sourcing based on an ethical approach, encouragement of the use of renewables, as well as community involvement in fulfilling sustainable objectives. Thus, the study also stresses the importance of clarity within communication channels and information reliability for the development of consumers’ trust. It defines factors like the cost and every person’s doubt or disbelief in what is green that prevents an extensive use of green products. Altogether, this research contributes useful knowledge for companies wanting to implement suitable green marketing initiatives that would be appealing to eco-aware consumers. It is clear that implementing corporate practice according to the customer expectation and practicing transparency would not only increase the brand value but also the customer loyalty and which in longer runs would also help in supporting and implementing sustainable development goals across the world.